2018
DOI: 10.1029/2017jd027422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Freshwater Flow From Rivers to the Sea in CMIP5 Simulations: Insights From the Congo River Basin

Abstract: Despite the multisectoral importance of water resources in the context of climate change, it remains still difficult to correctly simulate the terrestrial water cycle via general circulation and Earth system models. While existing model evaluation efforts from the Climate Model Intercomparison Project 5 (CMIP5) are mainly focused on atmospheric variables, we considered here the simulated freshwater flux into the ocean for the river Congo by 20 CMIP5 models. We found that many advancements are still required in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 116 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…This has been shown for metrics that employ precipitation data only (e.g., Standardized precipitation index [SPI]; Orlowsky and Seneviratne, 2013;Preethi et al, 2019), as well as metrics that combine precipitation and AED (e.g., PDSI; Zhao and Dai, 2017). The lack of CMIP5 model skill in reproduction near-present observations of hydrological drought has been shown in earlier works (e.g., Santini and Caporaso, 2018;Ukkola et al, 2018). However, other studies also confirmed the capabilities of CMIP5 models to capture the temporal variability and magnitude of observed soil moisture (e.g., Yuan and Quiring, 2017).…”
Section: Climate Modelsmentioning
confidence: 99%
“…This has been shown for metrics that employ precipitation data only (e.g., Standardized precipitation index [SPI]; Orlowsky and Seneviratne, 2013;Preethi et al, 2019), as well as metrics that combine precipitation and AED (e.g., PDSI; Zhao and Dai, 2017). The lack of CMIP5 model skill in reproduction near-present observations of hydrological drought has been shown in earlier works (e.g., Santini and Caporaso, 2018;Ukkola et al, 2018). However, other studies also confirmed the capabilities of CMIP5 models to capture the temporal variability and magnitude of observed soil moisture (e.g., Yuan and Quiring, 2017).…”
Section: Climate Modelsmentioning
confidence: 99%
“…The inlet approach, which defines a rectangular breach in coastal land cells with uniform density and discharge, is widely used (Herzfeld, 2015;Garvine, 2001). An additional barotropic pressure term may be added to account for pressure gradients induced by the freshwater plume (Schiller and Kourafalou, 2011). The inlet approach has also been used in global z-coordinate models by injecting freshwater in multiple vertical grid cells (Griffies et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as with the temperature biases, mesoscale processes are the possible error sources associated with coarse grid resolutions in salinity bias fields. Other sources of bias may be linked to the reproduction of the discharges of these rivers, arising from simulated precipitation by the continental process modules of the GCMs (Santini and Caporaso, 2018). Especially for GG, errors in the runoff of rivers or in precipitation values can be even more significant in SSS bias.…”
Section: Discussion Surface and Seasonal Cycles Biasesmentioning
confidence: 99%